Interdisciplinary investigation of naming practices of cafes signages in Jordan - Rababah, Mahmoud Ali; Rababah, Luqman M.; Abumelhim, Mohammad Husni; Abu-Melhim, Abdel-Rahman; Rababah, Khalid Ali (Penerbit Universiti Kebangsaan Malaysia, 2023)
Various studies have extensively examined the linguistic aspects of signage, especially in the context of store signs. However, scholarly research on Jordanian café culture is limited. Therefore, conducting a comprehensive study of Jordan's café scene is relevant and promising in providing valuable sociocultural insights. This research explores the sociocultural values, norms, and practices associated with café signs in Jordan. Three hundred forty café signs from various neighbourhoods in Amman provided the linguistic data for this research. The findings revealed that English predominates in café signage due to its liveliness, strong connection to globalisation, and favourable client perceptions. The data also showed that trendy café names and English cultural references enhance visibility. These establishments use alliteration, blending, compounding, and connotation techniques to attract customers. This study highlights the significance of English-language signage in Jordan and its implications for linguistic landscape research. Thus, the research proves beneficial for linguistic landscape researchers seeking insights into sociocultural values, norms, and practices in Jordanian society.